PENATALAKSANAAN FISIOTERAPI PADA KONDISI LOW BACK PAIN e.c SPONDILOSIS DENGAN MODALITAS TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN BACK EXERCISE DI RS ORTHOPEDI PROF. Dr. R. SOEHARSO SURAKARTA - Dwi Lia Octaviany; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Background: Lumbar spondylosis is a degenerative disease of the vertebral corpus or intervertebral disc. The problem of physiotherapy that arises in low back pain is pain, decreased muscle strength, limited range of joint motion, decreased functional activity. Pain check with VAS (Visual Analogue Scale), muscle strength with MMT (Manual Muscle Testing), joint motion range with midline functional activity with oswestry index. In this case the technology chosen to solve this problem is the modality of Transcutaneous Electrical Nerve Stimulation (TENS) and back excercise.      Objective: To determine the effect of Physiotherapy Management on Low Back Pain ec Spondylosis with Transcutaneous Electrical Nerve Stimulation (TENS) modalities and exercise therapy.Method: This study was conducted at the RSO Prof. Dr. R. Soeharso Surakarta with a descriptive analytical method to find out assessments and changes that can be known to use VAS instruments to examine pain, MMT to check muscle strength, midline to measure LGS, Oswestry to assess functional activity.Results: After 4 times the therapy was obtained, (1) There was a decrease in silent pain T1 = 3 at T4 = 2, tenderness T1 = 5 at T4 = 4, motion pain T1 = 6 at T4 = 5. (2) There is an increase in flexor muscle strength T1 = 4 at T4 = 5, the right lateral flexor muscle T1 = 3 at T4 = 4. (3) There is an increase in LGS with flexion difference T1 = 8 at T4 = 9, extension T1 = 4 T4 = 5, lateral flexion of the T1 = 12 T4 = 14. (4) There is an increase in functional activity from T1 = 60% T4 = 42.Conclusion: Physiotherapy inpatients with modalities and exercise therapy can reduce the problems that arise in the condition of Low Back Pain Spondilosys.